The Importance Of Moral Value Through Law Enforcement In Indonesia In Nonsystematic Legal Approach - Siti Zuliyah (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
ABSTRACT Objective: This writing is purposed to explore the importance of moral value through law enforcement in Indonesia as basic dispensing justice, which is essential through a nonsystematic legal approach. Methodology: This research using the philosophical approach method, which is purposed to explore the importance of moral value through law enforcement. As it for the method used in this research is descriptive, then proceeded in interpretive. Invention: Nonsystematical legal approach views that jurisprudence is living and developing behavior patterns in society so that between law and moral can not be separated. In relation to the importance of moral value through law enforcement is intended as guidelines for law enforcement officer in the act of implementing their job well and responsibly, so that can give justice. Purpose: This research can help explain the importance of moral value through law enforcement so that can be a formulation of regulation or guidelines for law enforcement officer about how should take action in implementing law enforcement that becomes responsible properly. Recency/Originality: In relation to law enforcement in Indonesia, have been struggling at the positivist paradigm or systematic that bring law out of value and religion, so that just being instrumentalist tools. Therefore needed a new approach by accommodate moral value and religion to law enforcement optimized. Keywords: Moral Value, Law Enforcement, Nonsystematic Legal Approach